Alkali and transition metal atom-functionalized germanene for hydrogen storage: A DFT investigation. (3rd June 2021) - Sosa, Akari Narayama; de Santiago, Francisco; Miranda, Álvaro; Trejo, Alejandro; Salazar, Fernando; Pérez, Luis Antonio; Cruz-Irisson, Miguel
Abstract: In this work, we have performed density functional theory-based calculations to study the adsorption of H2 molecules on germanene decorated with alkali atoms (AM) and transition metal atoms (TM). The cohesive energy indicates that interaction between AM (TM) atoms and germanene is strong. The values of the adsorption energies of H2 molecules on the AM or TM atoms are in the range physisorption. The K-decorated germanene has the largest storage capacity, being able to bind up to six H2 molecules, whereas the Au and Na atoms adsorbed five and four H2 molecules, respectively. Li and Ag atoms can bind a maximum of three H2 molecules, while Cu-decorated germanene only adsorbed one H2 molecule. Formation energies show that all the studied cases of H2 molecules adsorbed on AM and TM atom-decorated germanene are energetically favorable. These results indicate that decorated germanene can serve as a hydrogen storage system. Graphical abstract: Image 1 Highlights: The Li, Na and K atoms are binding strongest to germanene and avoid clustering. Na functionalized germanene have the largest storage capacity, 6H2 -molecules. Cu functionalized germanene is not a good candidate for hydrogen storage. Hydrogen molecules are physisorbed on metal atoms functionalized germanene. H2 -AM(TM)-germanene complexes are energetically more stable than H2 -germanene.